Cogongrass (Imperata cylindrica) Biology, Ecology, and Management in Florida Grazing Lands - Brent A. Sellers; Jason A. Ferrell; Gregory E. MacDonald; Kenneth A. Langeland; Stephen Luke Flory (EDIS)
Cogongrass is found on every continent and is considered a weedy pest in 73 countries. In the U.S., cogongrass is found primarily in the Southeast. It was accidentally introduced into Alabama in the early 1900s, and purposely introduced as a potential forage and soil stabilizer in Florida (and other states) in the 1930s and early 1940s. However, soon after investigations began it was realized that cogongrass could be a weedy pest. Since its introduction, cogongrass has spread to nearly every county in Florida. In some cases, it has completely taken over pastures so that it is the only species present. This is a common thread where cogongrass invades; it quickly displaces desirable species and requires intensive management. This revised 5-page fact sheet was written by B. A. Sellers, J. A. Ferrell, G. E. MacDonald, K. A. Langeland, and S. L. Flory, and published by the UF Department of Agronomy, August 2012.